EFEKTIVITAS MODEL KOOPERATIF TIPE NHT DENGAN PMR DAN MODEL KOOPERATIF TIPE GI DENGAN PMR TERHADAP PRESTASI BELAJAR MATEMATIKA DITINJAU DARI KREATIVITAS SISWA - Ardiawan, Yadi; Budiyono, Budiyono; Subanti, Sri (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aims of this research are to know: (1) which one gives better studentsâ mathematics achievement, cooperative model of NHT type with RME, cooperative model of GI type with RME or conventional model, (2) which one has better studentsâ mathematics achievement, student having high creativity, medium or low, and (3) for any level of creativities, which one gives better studentsâ mathematics achievement, cooperative model of NHT type with RME, cooperative model of GI type with RME or conventional model and for any kind of models which one has better studentsâ mathematics achievement, student having high creativity, medium or low. The type of this research was a quasi experimental by 3x3 factorial design.The population in this research was the seventh grade students of junior high school in Pontianak in the academic year 2012/2013. Sampling was done by stratified cluster random sampling. The instrument of research using mathematics achievement test and verbal creativity test. The conclusions of the research were as follows. (1) There is an influence of the learning model toward studentsâ mathematics achievement. Cooperative model of NHT type with RME providesÂ studentsâ mathematics achievement better than the cooperative model of GI type with RME and conventional model. Cooperative model of GI type with RME provides studentsâ mathematics achievement better than the conventional model. (2) There is an influence of the studentâs creativity level toward studentsâ mathematics achievement. Students having high creativity have better mathematics achievement than students having medium and low creativity. Students having medium creativity have better mathematics achievement than students with low creativity. (3) For any level of creativities that the cooperative model of NHT type with RME gives better studentâs mathematics achievement than cooperative model of GI type with RME and conventional model, and cooperative model of GI type with RME gives better studentsâ mathematics achievement than conventional model. For any kind of models, students having high creativity have better mathematics achievement than students having medium and low creativity, and students having medium have better mathematics achievement than students having low creativity. Keywords: Cooperative Model of NHT (Numbered Heads Together) type, Cooperative Model of GI (Group Investigation) type, RME (Realistic Mathematics Education) Approach, Studentâs Creativity